A Matter of Trust: Practical Strategies for Writing User-Centered, Values-Driven Description. Issue 3 (24th February 2022) - Hintz, Carrie; Quigley, Sarah
Abstract: An archives' descriptive practices have a significant impact on researchers' ability to find, use, and understand records. Archivists do not fully utilize the descriptive fields that DACS and other standards provide to explain how and why a collections are acquired and the interventions archivists make in collections. However, this information can be critical to a researcher's analysis. This paper makes a case for archival description that is rooted in values of transparency and accountability, and provides a concrete examples of how one institution rewrote its description policies to codify and formalize transparency and accountability as key drivers of their descriptive program.